Maintenance engineering handbook - Higgins, Lindley R.; Mobley, R. Keith 1943-; Smith, Ricky (Mc Graw Hill, 2001)
Provides science, technology, and management solutions for facility maintenance issues. This book focuses on: technology updates; improvements in prevention and prediction; equipment testing and monitoring tools; computer programs; advances in maintenance economics; guidance on insurance administration; and more.